PERTANGGUNGJAWABAN DAN DASAR PENGHAPUSAN PIDANA KORPORASI DI INDONESIA DITINJAU BERDASARKAN KUHP 2023 - Setiawan, Wawan; Said, Yusuf Muhammad (Neolectura, 2025)
This research aims to examine the criminal provisions for corporations in the Criminal Code 1946 and its improvement in Law No. 1 of 2023 (Criminal Code 2023). Along with the rapid globalisation and economic growth, crimes involving corporations are increasingly prevalent, such as environmental crimes, consumer protection, and money laundering. However, many corporations still escape criminal sanctions. Theories of corporate criminal liability, such as strict liability theory, vicarious liability theory, identification theory, and aggregation theory, are the basis for recognising corporations as legal subjects. This research uses a normative legal approach with statutory, conceptual, and case methods. The results show that the Criminal Code 1946 does not recognise corporations as subjects of criminal law, so that corporate criminal liability is only regulated in regulations outside the Criminal Code. Meanwhile, the Criminal Code 2023 has explicitly stipulated corporation as a subject of criminal law and regulated the mechanism of its liability. This reform provides a stronger legal basis in law enforcement against corporate crime.